PO 89 - Impacto da pandemia Sars-CoV-2 numa Unidade de Dor Aguda - Albuquerque Correia, Ana Filipa; Costa Gomes, Piedade; Vaz, Mariana; Vieira, Ana Luísa; Cruz, Margarida; Cruz, Daniela (Journal of the Portuguese Society of Anesthesiology, 2023)
x